Effectiveness of a novel polyaniline@Fe-ZSM-5 hybrid composite for Orange G dye removal from aqueous media: Experimental study and advanced statistical physics insights. (May 2022) - Imgharn, Abdelaziz; Anchoum, Lahoucine; Hsini, Abdelghani; Naciri, Yassine; Laabd, Mohamed; Mobarak, Mohamed; Aarab, Nouh; Bouziani, Asmae; Szunerits, Sabine; Boukherroub, Rabah; Lakhmiri, Rajae; Albourine, Abdallah
Abstract: A polyaniline@Fe-ZSM-5 composite was synthesized via an in situ interfacial polymerization procedure. The morphology, crystallinity, and structural features of the as-developed PANI@Fe-ZSM-5 composite were assessed using scanning electron microscopy – energy dispersive spectroscopy (SEM-EDS), X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, and X-ray photoelectron spectroscopy (XPS). The composite was efficiently employed for the first time as an adsorbent Orange G (OG) dyestuff from water. The OG dye adsorption performance was investigated as a function of several operating conditions. The kinetic study demonstrated that a pseudo-second-order model was appropriate to anticipate the OG adsorption process. The maximum adsorption capacity was found to be 217 mg/g. The adsorption equilibrium data at different temperatures were calculated via advanced statistical physics formalism. The entropy function indicated that the disorder of OG molecules improved at low concentrations and lessened at high concentrations. The free enthalpy and internal energy functions suggested that the OG adsorption was a spontaneous process and physisorption in nature. Regeneration investigation showed that the PANI@Fe-ZSM-5 could be effectively reused up to five cycles. The main results of this work provided a deep insight on the experimental study supported by advanced statistical physics prediction for the adsorption of Orange G dye onto the novel polyaniline@Fe-ZSM-5 hybrid composite. Additionally, the experimental and advanced statistical physics findings stated in this study may arouse research interest in the field of wastewater treatment. Graphical abstract: Image 1 Highlights: A novel PANI@Fe-ZSM-5 hybrid composite was easily elaborated and fully characterized. The adsorption performance of PANI@Fe-ZSM-5 towards OG dye was investigated. The OG dye binding mechanism was assessed by advanced statistical physics modeling. Statistical physics parameters and thermodynamic functions of the adsorption system were studied. PANI@Fe-ZSM-5 composite has excellent adsorption ability and satisfactory reusability.